Effect of Enzymatic Hydrolysis on the Zinc Binding Capacity and in vitro Gastrointestinal Stability of Peptides Derived From Pumpkin (Cucurbita pepo L.) Seeds - Lu, Dan; Peng, Mengyao; Yu, Min; Jiang, Bo; Wu, Hong; Chen, Jingjing (Frontiers in Nutrition, 2021)
Zinc is a crucial micronutrient in human for maintaining normal body function that participated in many important enzymatic reactions. However, insufficient intake from diet may lead to zinc deficiency and impair normal body function. Besides, conventional zinc salts supplementation has the disadvantage of low digestibility since the zinc ions may be easily chelated by dietary fiber or phytate commonly found in vegetable diets, and form precipitates that cannot be absorbed. Therefore, the objective of the present study is to prepare pumpkin seed derived peptides and to evaluate the effect of structure and surface hydrophobicity on the zinc binding behavior of these pumpkin seed protein hydrolysate (PSPH), as well as their gastrointestinal stability. Briefly, different PSPHs were prepared using enzymatic hydrolysis with alcalase, papain, flavourzyme, bromelain and trypsin. The particle size, zeta potential, surface hydrophobicity, degree of hydrolysis, FTIR spectra and zinc binding capacity was determined. The representative samples were chosen to characterize the binding energy and surface morphology PSPH-Zn. At last, the in vitro gastrointestinal stability of PSPH-Zn was evaluated. Our result showed that peptides hydrolyzed by papain had the smallest average molecular weight and particle size, the highest hydrophobicity and the greatest zinc binding capacity. The result of this study indicated pumpkin seed may be used as a good source for zinc. The findings in this study may provide important implications for developing plant-based zinc chelating peptides.